Physical Therapist and Physical Therapist Student Knowledge, Confidence, Attitudes, and Beliefs About Providing Care for People With Dementia: A Mixed-Methods Systematic Review. Issue 5 (12th February 2022) - Quick, Stephen M; Snowdon, David A; Lawler, Katherine; McGinley, Jennifer L; Soh, Sze-Ee; Callisaya, Michele L
Abstract: Objective: The purpose of this study was to determine physical therapists' and physical therapist students' attitudes and beliefs, knowledge, and confidence in working with people with dementia. Methods: This was a mixed-methods systematic review. Participants included physical therapists working in any clinical specialty and physical therapist students who had completed at least 1 clinical placement. Eleven databases were searched. The evidence was evaluated using the Joanna Briggs Institute Critical Appraisal Checklists. Data synthesis followed a convergent integrated approach according to Joanna Briggs Institute methodology for mixed-methods systematic reviews. Quantitative data were "qualitized" using thematic analysis and synthesized with qualitative data using thematic synthesis. Results: Fifteen studies were included (9 quantitative and 6 qualitative studies). Seven key themes evolved. Five related to the belief that (1) working with people with dementia is complex and challenging; (2) opportunities for education in dementia care are lacking; (3) working with people with dementia is a specialized area of practice; (4) there are unsupportive systems for working with people with dementia; and (5) people with dementia deserve rehabilitation, but their potential to improve is less certain. One theme related to knowledge (lack of knowledge in some areas of dementia care), and 1 theme related to confidence (lack of confidence in working with people with dementia). Conclusions: Physical therapists and physical therapist students believe that working with people with dementia can be challenging. The low levels of knowledge and confidence in areas important to working with people who have dementia suggest that more education about dementia is needed. Impact: This mixed-methods systematic review highlights that physical therapists and physical therapist students believe that working with people who have dementia is complex and challenging. Physical therapists want more training and support in this growing area of practice.